How Does Intellectual Capital Affect Firm Performance Across Different Levels? A Quantile Regression Approach - Yusup, Adi Kurniawan (Management Analysis Journal, 2024)
This study aims to examine the effect of intellectual capital on firm performance. Intellectual capital is evaluated using the Value-Added Intellectual Coefficient (VAIC), which covers human, structural, and capital efficiency. Using quantile regression and three different performance measures, the study analyzes how the effect of intellectual capital changes across different performance levels. The sample is 358 Indonesian non-financial companies (1,074 firm-year observations) from 2018 to 2020. The results show a positive relationship between intellectual capital and firm performance, which supports the resource-based theory (RBT). However, the effect varies between high-performing and low-performing companies, showing that intellectual capital has a different influence depending on the firm's performance level.